Ameliorative impacts of Rhodiola rosea against hepatic toxicity induced by monosodium glutamate: role of inflammation-, oxidative-stress-, and apoptosis-associated markers - Mohamed Mohamed Soliman; Saed A. Althobaiti; Samy Sayed (Journal of Taibah University for Science, 2023)
Current study examined the protective impact of Rhodiola rosea (R. rosea) extract on hepatic toxicity markers caused by MSG. MSG induced significant increases in hepatic stress biomarkers. There were significant declines in GSH, catalase and SOD levels, which were accompanied by substantial elevations in IL-1β, IL-6, and TNF-α. There was hepatic cellular damage, and upregulation of caspase-3 and a decrease in Bcl-2 expression. The hepatotoxic impacts of MSG were normalized by Rhodiola supplementation. R. rosea downregulated caspase-3 and upregulated HO-1 and Nrf2 mRNA expression. R. rosea regulated the immunoreactivity of COX-2, TGF-β1, and NFkB genes associated with hepatic toxicity. R. rosea extract normalized histopathological changes induced by MSG and restored hepatic architecture. R. rosea extract exhibited anti-apoptotic, antioxidant, and anti-inflammatory properties. In conclusion, R. rosea extract is a promising medication against hepatic toxicity induced by MSG, which works by regulating the different signaling pathways of inflammation-, oxidative-stress-, and apoptosis-associated markers.